Modelling Malaysian road accident deaths : an econometric approach / Wan Fairos Wan Yaacob and Wan Zakiyatussariroh Wan Husin - Wan Yaacob, Wan Fairos; Wan Husin, Wan Zakiyatussariroh (Institute of Research, Development and Commercialization (IRDC), 2006)
A number of methods have been proposed for dealing with road accident death model. This paper uses econometric regression models to develop the road accident death model. By using this approach, this paper attempts to establish a statistical model to describe the relationship between the total road accident deaths and a range ofexplanatory macroeconomic variables. The macroeconomic factors used in the model include population, the number of registered vehicles, road length, technique of data coverage, system of data recording and Gross Domestic Product. The results suggest that the POp, ROADL, VEH and DR do not have any impact on road accident deaths. In contrast, the GDP and Technique of data Coverage were found to be highly significant (P < 0.05) in explaining the road accident deaths.